ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. D DI BPM TUGIRAH, A.Md. Keb. DESA WONOSARI KEC. KEBUMEN KAB. KEBUMEN - Annisa Budi Utami (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2022)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are indicators of health status. Health problems in Indonesia are mainly caused by the high rate of maternal and infant mortality. To make a real contribution in reducing MMR and IMR, the author provides comprehensive midwifery care from pregnancy, childbirth, postpartum, newborn and family planning. The purpose of this study is to provide quality services with comprehensive midwifery care through Varney's 7-step midwifery management approach. The method of this research is descriptive observational at BPM Tugirah. Data was collected through interviews, observation, examination and documentation. Case study analysis with 7 Varney steps. The results of the case report and the discussion of this research are implementing and providing comprehensive midwifery care to Ny. D from pregnancy, childbirth, postpartum, newborn, neonates and family planning. While providing midwifery care there were no complications for Mrs. D and there is a gap between theory and practice in the field, the midwife's pregnancy examination using 10T, and the implementation of normal delivery care the midwife uses 58 steps.